Morphometric increase of tree species submitted to fertilization with swine wastewater - Pellá, Matheus Galdioli; Araújo, Gabriel Viana de; Cordeiro, Juliano (Scientia Agraria Paranaensis, 2018)
Swine is an important exploration of Paraná’s cattle raising, promoting the generation of employment and income in rural areas, however, it generates large amounts of solid and liquid residues. Based on these considerations, the objective of this work was to analyze the development of native tree species submitted to fertilization with swine wastewater. Four native tree species were selected: Anadenanthera colubrina (Vell.) Brenan (Fabaceae), Astronium graveolens Jacq. (Anacardiaceae), Cordia trichotoma (Vell.) Arráb. ex Steud (Boraginaceae) and Heliocarpus popayanensis Kunth (Malvaceae). The applied doses of wastewater had been of 0, 25 and 50 m3 ha-1. They were applied every two months, adding up a total of 6 applications and the measured morphometric variables of the seedlings were height (cm) and stem diameter (mm); the experimental design selected was completely randomized design and samples of the witness plots were collected in order to assess the chemical conditions of the soil. For the height variable only the species Astronium graveolens was statistically different from the others. With respect to stem diameter, it was found that Heliocarpus popayanensis presented the highest average, but it was statistically similar to Cordia trichotoma, however, differing significantly from the others. The use of swine wastewater as a fertilizer is a good option to optimize the growth of native species in question, especially the 25 m3 ha-1 dose of swine wastewater, because it was the treatment that presented the best results of the increment values of both morphometric variables measured.